2015
DOI: 10.1177/0363546515572769
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disturbance Associated With Rotator Cuff Tear

Abstract: Sleep disturbance is common in patients undergoing rotator cuff repair. After surgery, sleep disturbance improves to levels comparable with those of the general public. Preoperative and prolonged postoperative use of narcotic pain medication negatively affects sleep.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
83
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(98 citation statements)
references
References 5 publications
2
83
0
2
Order By: Relevance
“…Rapid improvement in sleep seen as early as 6 weeks after surgical treatment for LSS is noteworthy. According to the studies that examined changes in sleep after surgical treatment for osteoarthritis of the knee and rotator cuff tear, sleep worsened 6 weeks after surgery, and significant improvement was only achieved 3 months after surgery 23 , 24 . However, in our cohort, global PSQI scores decreased as early as 6 weeks after surgical treatment (12.3–6.7, Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid improvement in sleep seen as early as 6 weeks after surgical treatment for LSS is noteworthy. According to the studies that examined changes in sleep after surgical treatment for osteoarthritis of the knee and rotator cuff tear, sleep worsened 6 weeks after surgery, and significant improvement was only achieved 3 months after surgery 23 , 24 . However, in our cohort, global PSQI scores decreased as early as 6 weeks after surgical treatment (12.3–6.7, Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional studies investigated the quality of sleep in other musculoskeletal diseases such as osteoarthritis of the knee, and rotator cuff tear 21 , 22 , and recent prospective case-series measured their changes after surgical treatment 23 , 24 . In such joint diseases, pain is generally reduced during sleep, because the gravitational joint force is decreased in the lying position.…”
Section: Introductionmentioning
confidence: 99%
“…‡ Associations have been made between sleep disturbance and chronic neck and back pain, 1 , 12 , 14 knee pain, 17 carpal tunnel syndrome, 18 , 19 long-bone fractures, 22 and shoulder abnormalities, 6 , 16 including shoulder impingement syndrome 23 and rotator cuff tears. 3 , 16 To our knowledge, there has only been one study to find that pain levels in patients with shoulder impingement syndrome directly correlated with sleep quality. 23 However, others have demonstrated that sleep disturbance is more strongly associated with poor emotional status and ineffective coping strategies and less dependent on symptom intensity or functional status.…”
mentioning
confidence: 99%
“…A previous study found that sleep disturbance is 3 to 6 times more common in patients with rotator cuff tears than the general population. 1 Poor sleep is often a salient factor in these patients’ decisions to seek care. Arthroscopic repair has been associated with improved sleep quality in many patients with full-thickness rotator cuff tears 1 ; however, some individuals continue to suffer from sleep disturbance postoperatively.…”
mentioning
confidence: 99%
“…1 Poor sleep is often a salient factor in these patients’ decisions to seek care. Arthroscopic repair has been associated with improved sleep quality in many patients with full-thickness rotator cuff tears 1 ; however, some individuals continue to suffer from sleep disturbance postoperatively. Previous studies have reported that up to 41% of patients continue to have poor sleep quality following repair of a full-thickness tear.…”
mentioning
confidence: 99%